Risk shocks and housing markets - Viktor Dorofeenko; Gabriel S. Lee; Kevin D. Salyer (Institute for Advanced Studies (IHS), 2010)
This paper analyzes the role of uncertainty in a multi-sector housing model with financial frictions. We include time varying uncertainty (i.e. risk shocks) in the technology shocks that affect housing production. The analysis demonstrates that risk shocks to the housing production sector are a quantitatively important impulse mechanism for the business cycle. Also, we demonstrate that bankruptcy costs act as an endogenous markup factor in housing prices; as a consequence, the volatility of housing prices is greater than that of output, as observed in the data. The model can also account for the observed countercyclical behavior of risk premia on loans to the housing sector.
Keywords: E4; E5; E2; R2; R3; 330; agency costs; credit channel; time-varying uncertainty; residential investment; housing production; calibration; Immobilienpreis; Technischer Fortschritt; Wohnungsbau; Entscheidung bei Unsicherheit; Zeitpräferenz; Risikoprämie; Hypothek; Schätzung; USA